The New Wave of Capital Inflows: Sea Change or Tide? - Eduardo Fernández-Arias (Inter-American Development Bank, Research Department, 2000)
Will capital inflows boom again in Latin America as countries recover from the 1998-99 recession? And will they bust again shortly thereafter, repeating the cycle of the past? Is there something fundamentally different about the new wave of capital inflows to alter this historical pattern, a sea change in the way the region is financially linked to international capital markets? Or is nothing really new under the sun and will the new wave of capital inflows be just another tide, bringing in its wake a capital withdrawal and a financial market drought? This paper addresses these important issues, over which there is much controversy.
Keywords: 330; Kapitalimport; Internationaler Finanzmarkt; Lateinamerika; Finanzkrise